Launch of Master’s program (M.Sc.) in Health Economics and Statistics in Taras Shevchenko National University of Kyiv - Kovtun, N. V.; Kolodyazhna, O. I.; Babin, K. V. (Statistics of Ukraine, 2020)
Health Economics has now evolved into a complex science that is based on related disciplines, including epidemiology, statistics, psychology, sociology, operations research, and mathematics. Thus, Health Economics is a set of economic and statistical disciplines that serve as the basis for decision-making by healthcare providers and governments. It also includes a set of analytical methods used in the analysis of the healthcare market. Health Economics and Statistics is a modern master’s program with the main objective to prepare statistics specialists who are able to solve complex problems, make appropriate analytical decisions in the field of clinical research and management decisions in the field of public health that involves conducting research and fostering innovation in the face of uncertainty. Studying statistical methods enables students to acquire up-to-date analytical skills applied to clinical research and healthcare management. The objectives of the Master’s program are focused on providing students with the necessary information about international clinical research experience, forming a critical understanding of the pricing process on the healthcare market, as well as the mechanism for reimbursement of medical expenses in the world. In addition, the program will provide students with an understanding of the organization of existing health systems and methods needed to analyze health policies. The advantages of the program are tied to the goals of the acquisition of applied statistical analysis skills, which is an indispensable requirement of high qualification of an analyst in clinical research and public health. This is ensured by: 1) integration of practice with academic training; 2) the opportunity to contribute to the development of one's own potential; 3) expanding the capacity for scientific research; 4) the opportunity to defend a master’s thesis, working on a real project; 5) providing real career perspectives. Thus, the implementation of this program will provide an opportunity to prepare highly qualified specialists – analysts in the field of clinical research and public health. Specialists who are in high demand in the private sector (clinical research market) on the national and international level, in the national, regional and local NGOs and institutions in positions related to the planning, collection, processing, and analysis of clinical and public health data, as well as evaluating the quality of managerial decisions in healthcare. All of this, in turn, will help to ensure the competitiveness of specialists and increase the prestige of the specialty.